Analisis Pelaksanaan Administrasi Waris Di Kecamatan Plaju Kota Palembang - Nurmalena, Nurmalena; Syuroh, Mat; Hestirinaih, Deby Chintia (@-Publik: Jurnal Administrasi Publik, 2025)
Implementation of District Integrated Administration (PATEN) is defined as sub-district activities in providing public services, where the procedures for submitting applications and controlling documents take place at one counter or service point. ) covers the licensing sector, in this case business permits, as well as house building services and non-licensing services, in this case for example making succession certificates. The existence of the District Integrated Administration Administration (PATEN) program can facilitate heir deed services for the community, showing enthusiasm from the community. The inheritance deed service is first carried out at the village/district office by bringing complete documents and certain conditions, and a court order is not used for implementation. The aim of this research is to analyze the implementation of historical heritage protection in Plaju sub-district, Palembang city. The problems identified are: Many people do not understand the meaning and completeness of the requirements for making a succession certificate through the District Integrated Administration Program (PATEN) AND the time required to take care of succession matters is quite long. The data analysis technique used in this research is a qualitative data analysis technique. This research shows that: overall the implementation of historical heritage conservation in the Plaju Palembang area is going well